SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA TURUNAN KALKON PADA STRAIN BAKTERI Bacillus subtilis DAN Escherichia coli - Ayik Rosita Puspaningtyas (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
Disease caused by bacteria still have a high prevalence in Indonesia, both in urban and rural areas. Currently the treatment of diseases caused by bacteria carried by many antibiotics, whereas in reality antibacterial drugs like antibiotics are now causing a lot of resistance in some people. Because of this we effort to develop antimicrobial agents, a series of chalcones were 1-(4-Bromo-phenyl) -3-(4-methoxy-phenyl)-2-propen-1-on and 1-(4- Bromo-phenyl)-3-(3,4-dimethoxy-phenyl)-2-propen-1-on compounds.These compounds are synthesized on the basis of QSAR (Quantitative Structure Activity Relationships) using lipophilic, steric, and electronic parameters. Compound 1-(4-Bromo-fenill)-3-(4-methoxy-phenyl)-2-propen-1-on and 1-(4-Bromo-phenyl)-3-(3,4-dimethoxy-phenyl)-2-propen-1-on is made from raw materials 4-bromo-asetophenone and 4-Methoxy benzaldehide/3,4-dimethoxy benzaldehide usual Claisen-Schmidt condensation method of mixing for overnight 24 hours then be recrystallized to obtain a pure crystalline chalcones analog compounds. After the synthesis, compounds were characterized by organoleptic and melting point test. The results showed that a white color, smells aromatic, and needle crystals. The synthesized compounds were characterized by means of their 1H-NMR spectral data. All the compounds were tested for their antibacterial activities by the hole plate method.